Peran Masyarakat Sipil Dalam Proses Demokratisasi - Hadi, Otho H. (UI Scholars Hub, 2010)
The growth of civil society in Indonesia gives rise to some imperative issues to resolve. This is the indispensable ground why the study is carried out, i.e. the contribution of the role of civil society on the process of democratization undergone todate. The objectives of this study are among others to identify problems faced by civil society organisation in instigating its role with regard to the aspects of enabling environment (external) and capacity of organisation (internal) as well as the nature enhancement; to acquire profile of civil society augmentation in the context of its role contribution as significant actor democracy advancement, and to propose policy recommendation concerned with contribution and enhancement of the role of civil society in the process of consolidating democracy in Indonesia. This study is a qualitative review. The methods used are among others depth interview, focused group discussion, public consultation through seminar, and literature study to identify CSOs that will be the target of this study. The study concludes that (1) state-civil society relationship is enormously influenced by local context (social and political culture), nature of civil society organisation (human resources and management, financial sources, movement model, networking), and local and national political economy dynamic; (2) civil society organisation has an important potential on the process of consolidating democracy in Indonesia; (3) the role of society in generating the growth of civil society organisation has been somewhat noteworthy.